RELATIONSHIP BETWEEN THE HEALTH AND MEDIA LITERACY - SAĞLIK VE MEDYA OKURYAZARLIK ARASINDAKİ İLİŞKİ - Şerife Didem Kaya; Ayhan Uludağ (Mehmet Akif Ersoy Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Health literacyand media literacy are important indicators for development a region. Aim ofthe study was to determine the health and media literacy levels of people andthe relationship between two types of literacy in Mut County, Mersin/Turkey. A cross-sectional survey was conducted among275 people using a standard questionnaire. The questionnaire includesrespondent’s socio-demographic background, media literacy level determinationscale and SOYA-AB scale. It wasfound that general index score for healthliteracy was 35.99 in Mut province. It was determined that 10% of the participantswere “inadequate”, 27 % of them were problematical and % 23 of the respondentswas excellent in term of general health literacy. Total media literacy level ofthe participants was 3.89. A positive and medium level relationship was foundbetween health literacy and media literacy levels. The participants had anaverage knowledge on the health and media literacy level in Mut province.